2017
DOI: 10.1002/ep.12617
|View full text |Cite
|
Sign up to set email alerts
|

Dye removal from wastewater by the cross‐linked blend nanofiber and homogenous surface diffusion modeling

Abstract: In this paper, the blend nanofiber (poly(vinyl alcohol) (PVA)/chitosan (CS)/diethylenetriamine (DETA)/ethylenediamine (EDA): PVA/CS/DETA/EDA) was prepared by electrospinning and cross‐linked by glutaraldehyde. The cross‐linked blend nanofiber by glutaraldehyde (CBNG) was characterized by FTIR and SEM. The homogenous surface diffusion model (HSDM) was used for expressing the dye adsorption on CBNG from colored wastewater. Experimental data were used to calculate the isotherm parameters as well as the kinetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(91 reference statements)
3
3
0
Order By: Relevance
“…Sparks has reported that without spectroscopic evidences, it is very difficult to interpret sorption mechanisms simply from time dependent data . However, in the present study we suggest that the initial rate of reaction is controlled by the surface reaction, like adsorption and surface precipitation, in line with explanation given in the earlier sections on the basis of FTIR findings and SEM images after MB sorption, which are then changed to intraparticle diffusion into the pores of the biosorbent .…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Sparks has reported that without spectroscopic evidences, it is very difficult to interpret sorption mechanisms simply from time dependent data . However, in the present study we suggest that the initial rate of reaction is controlled by the surface reaction, like adsorption and surface precipitation, in line with explanation given in the earlier sections on the basis of FTIR findings and SEM images after MB sorption, which are then changed to intraparticle diffusion into the pores of the biosorbent .…”
Section: Resultssupporting
confidence: 91%
“…Figure shows the effect of temperature on the sorption of cationic MB by Solanum xanthocarpum fruit powder, where it is evident that by increasing the temperature of the system from 293 to 323 K, the uptake of MB increases both at pH 4 and 6, showing the sorption process to be endothermic. Similar increase in the sorption of cationic dyes and other cations from aqueous solutions, with increasing temperature has been reported in a number of previous studies . By increasing the temperature from 293 to 323 K, the sorption of MB increases drastically at pH 6, while at pH 4, there is a gradual increase in its sorption with increasing temperature and concentration.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations